Effects of 60Co-γ Ray Irradiation on the Quality of Ponkan Peels - WANG Xue, PAN Zhaoping, LI Wenge, SU Zhipeng, CHEN Jiaxu, HE Shuang, FU Fuhua (Shipin Kexue)
To investigate the effect of different doses of 60Co-γ ray irradiation on the quality of ponkan peels, the major functional components of irradiated ponkan peels were determined by ultraviolet-visible (UV-Vis) spectrophotometry and high performance liquid chromatography (HPLC). The volatile components were analyzed qualitatively and quantitatively using headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS). The results showed that irradiation affected the major functional constituents of ponkan peels. Treatment with a certain dose of irradiation increased the contents of total phenol, total flavonoid, nobiletin and tangeretin while decreasing the contents of hesperidin, gallic acid and ferulic acid, but had no significant effect on caffeic acid or chlorogenic acid. The irradiation treatment had a significant effect on the aroma constituents of ponkan peels, resulting in a decrease in the percentage, type and content of olefinic substances and an increase in the contents of alcohols, phenolic acids and aldehydes and ketones. Totally 51 new aroma substances were formed after irradiation treatment, and the odor activity value (OAV) showed that linalool, limonene and n-octanal were the key aroma substances of irradiated ponkan peels, indicating that 60Co-γ ray treatment accelerated the aging of ponkan peels. In addition, principal component analysis (PCA) showed that the quality of ponkan peels varied with different irradiation doses, the highest overall evaluation score being observed for ponkan peels irradiated at 4 kGy. This study provides a reference for accelerating the aging of Pericarpium Citri Reticulatae as well as a basis for the development and utilization of Pericarpium Citri Reticulatae products.